2021
DOI: 10.3390/ijms22158130
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Different Mitochondrial Oxidative Phosphorylation Components to the Retinal Pigment Epithelium Barrier Function: Implications for RPE-Related Retinal Diseases

Abstract: Disruption of retinal pigment epithelial (RPE) barrier integrity is involved in the pathology of several blinding retinal diseases including age-related macular degeneration (AMD) and diabetic retinopathy (DR), but the underlying causes and pathophysiology are not completely well-defined. Mitochondria dysfunction has often been considered as a potential candidate implicated in such a process. In this study, we aimed to dissect the role of different mitochondrial components; specifically, those of oxidative pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…When comparing the effects of the three mitochondrial inhibitors on the various resistance parameters between RPE cells in our previous study [ 17 ] to HRECs in the present work, there are key similarities and differences that need to be highlighted. In RPE cells, rotenone disrupted R b in a dose-dependent fashion, while in HRECs, we showed that a single concentration of 1 µM rotenone completely abolished R b .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When comparing the effects of the three mitochondrial inhibitors on the various resistance parameters between RPE cells in our previous study [ 17 ] to HRECs in the present work, there are key similarities and differences that need to be highlighted. In RPE cells, rotenone disrupted R b in a dose-dependent fashion, while in HRECs, we showed that a single concentration of 1 µM rotenone completely abolished R b .…”
Section: Discussionmentioning
confidence: 98%
“…The effect of different inhibitors targeting different steps in mitochondrial OxPhos on the cellular barrier functionality of HRECs was evaluated by measuring the overall impedance [Z; ohms (Ω)] using ECIS ® Zθ (theta) biosensor technology (Applied Biophysics Inc., Troy, NY, USA) followed by mathematical modeling as described previously [ 16 , 17 ]. Before seeding the cells, the electrode substrate array of the 96-well plate (96W20idf PET, Applied Biophysics, Inc.) was prepared by coating with 50 µL of 100 µM cysteine (Applied Biophysics) for 30 min, followed by aspiration.…”
Section: Methodsmentioning
confidence: 99%
“…ROS (superoxide radicals) appear in the RPE during ER stress as a byproduct of oxidative phosphorylation, which occurs largely in the mitochondria. Superoxide radicals are massively generated in dark processes of the mitochondrial respiratory chain, as well as by exposure to visible light [ 94 , 95 ].…”
Section: The Maintenance Of Redox Homeostasis In Rpe Cellsmentioning
confidence: 99%
“…Mitochondrial OS in the RPE leads to metabolic dysfunction in both the RPE and retinal photoreceptors [ 95 , 101 ]. Mitochondrial DNA is more susceptible to oxidative damage in neuropathologies [ 102 ].…”
Section: The Maintenance Of Redox Homeostasis In Rpe Cellsmentioning
confidence: 99%